Recent advances of carbon nanotubes in perovskite solar cells - Xian‐Gang Hu; Zhenhua Lin; Liming Ding; Jingjing Chang (SusMat, 2023)
Abstract Perovskite solar cells (PSCs) have exhibited tremendous potential in photovoltaic fields owing to their appreciable performance and simple fabrication. Nevertheless, device performances are still required to be further improved before commercial applications. As one‐dimensional materials, carbon nanotubes (CNTs) have been utilized to regulate stability and efficiency of PSCs because of their excellent chemical stability, flexibility, as well as tunable optical and electrical characteristics. In this review, we comprehensively summarize various functions of CNTs in PSCs, such as transparent electrodes, hole/electron‐transport layers, counter electrodes, perovskite additives, and interlayers. Additionally, applications of CNTs toward the advancement of flexible and semitransparent PSCs are provided. Finally, we preview the challenges and research interests of using CNTs in high‐efficiency and stable perovskite devices.